m² + 5m + 9
(- 2)² + 5( - 2) + 9 =
4 + (- 10) + 9 =
4 - 10 + 9 =
-6 + 9 =
3
- - - - - - - - -s-
2007-02-12 06:44:03
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
m² + 5m + 9
= (-2)² + 5 x (-2) + 9
= 4 -10 + 9
= 3
2007-02-12 06:12:48
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
m2 + 5m + 9
As m = -2.
(-2)^2 + 5(-2) + 9
= 4 +(-10) + 9
= 4 - 10 + 9
= -6 + 9
= 3
That's the answer....!!!!
2007-02-12 06:11:56
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
3
2007-02-12 06:07:45
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Wherever you see an "m", put a -2 in it's place.
m2 + 5m + 9 when m = -2
(-2)2 + 5 (-2) + 9
A negative times a positive is always negative
(-2)2 = -4
Same with the next part
5(-2) = -10
Put the two negatives together:
-4 + -10 = -14
Add this answer to 9
-14 + 9 = 5
The answer is 5!
2007-02-12 06:18:32
·
answer #5
·
answered by Nate 5
·
0⤊
0⤋
m^2 + 5m + 9 when m =-2
=> (-2)^2 + (5x-2) + 9
=> 4 - 10 + 9
= 3
2007-02-12 06:07:27
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
Hmm.
m2 + 5m + 9
4 - 10 + 9
3
2007-02-12 06:10:55
·
answer #7
·
answered by Anonymous
·
1⤊
0⤋
(-2)² + 5(-2) + 9
4 - 10 + 9
3
2007-02-12 06:07:12
·
answer #8
·
answered by bequalming 5
·
0⤊
0⤋
-5
2007-02-12 06:09:41
·
answer #9
·
answered by jrguth5 2
·
0⤊
0⤋
-5
2007-02-12 06:08:32
·
answer #10
·
answered by JUST ME 3
·
0⤊
0⤋